Global halal SMEs: principles & potentials - Abdullah, Moha Asri (2019)
As Malaysia is becoming a high-income nation, one of the strategies is to increase the country’s Gross Domestic Product (GDP). It was recorded that in 2016, the direct sales industry contributed RM17 billion to the country’s gross domestic product (GDP), more than double compared to RM8.03 billion in the year 2006. Halal industry has created more opportunities and spaces for Halal Small and Medium Enterprises (SMEs) to grow, and expand not just in Malaysia but more importantly in global market. Unfortunately, Bumiputera economic participation in the SMEs and in the Halal industry has been relatively low. Record shows that only 27.6 percent out of 1,026,000 registered companies in Malaysia are Bumiputera-owned companies. The word halal is rooted from an Arabic word which means ‘permissible’ or ‘lawful’ according to the Islamic rules and regulations. The concept of halal is not bound to food-related items only but to multiple other aspects such as products, which can be further categorized into various groups, for instance, cosmetics, self-care, health, and services for example, banking, tourism and others. Despite the booming Halal market, the SME sector of Bumiputera Business Community in Malaysia has not shown its full potential as it stumbles with multiple issues and challenges. This needs attention from various stakeholders to work together to help transforming and strengthening the sector to successfully tap the market potential.